Jesus as the son of 1-2 Samuel's David: an intertextual reading of the Gospel of Matthew - Grønbech-Dam, Marc (Biblical interpretation series, 2024)
Although the Gospel of Matthew emphasizes Jesus as the son of David, no one has systematically investigated how 1-2 Samuel influence Matthew's portrayal of Jesus as the son of David. This work addresses that lacuna and shows how the sustained use of 1-2 Samuel in Matthew evokes the themes of mercy and righteousness as the hallmarks of a proper Davidic shepherd. The book's systematic intertextual and narrative approach offers another way to understand Matthew’s Christology and portrayal of the kingdom of heaven. It helps the reader appreciate the justice-focused nature of Jesus’ rule and its religious and political implications.